2021
DOI: 10.21037/atm-21-1130
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes in STEMI patients with high thrombus burden treated by deferred versus immediate stent implantation in primary percutaneous coronary intervention: a prospective cohort study

Abstract: Background: No-/slow-reflow indicates worse outcomes in ST-elevation myocardial infarction (STEMI) patients with high thrombus burden. We examined whether deferred stenting (DS) strategy reduces no-/ slow-reflow or major adverse cardiovascular events (MACEs) in primary percutaneous coronary intervention (pPCI) for patients with acute STEMI and high thrombus burden. Methods:We performed an open-label, multi-center, prospective cohort study among eligible patients with acute STEMI and high thrombus burden who fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…What's more, a substantial number of patients had slow or no-reflow before stenting in this study. In our follow-up study ( 29 ), we found that the no-/slow-reflow event guided by thrombolysis in myocardial infarction (TIMI) flow grade occurred in 38 (15.5%) of the 245 STEMI patients. It was quite a high rate, so the influence of slow reflow cannot be ignored.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…What's more, a substantial number of patients had slow or no-reflow before stenting in this study. In our follow-up study ( 29 ), we found that the no-/slow-reflow event guided by thrombolysis in myocardial infarction (TIMI) flow grade occurred in 38 (15.5%) of the 245 STEMI patients. It was quite a high rate, so the influence of slow reflow cannot be ignored.…”
Section: Discussionmentioning
confidence: 94%
“…Firstly, this study reflected the experience with a limited number of patients. Since IVUS is not routinely used in pPCI of STEMI in clinical work, the sample sizes of previous studies that focused on IVUS, vascular physiology, and STEMI are generally small ( n = 117, Geng; n = 51, Luo, D) ( 27 , 29 ). To increase the sample size, minimize the bias, and improve reliability, this study was designed as a multicenter clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…The study was a multicentre prospective cohort study, and the design of this study was previously described ( 19 ). The study was registered at the Chinese Clinical Trial Registry (registration number: ChiCTR1800019923).…”
Section: Methodsmentioning
confidence: 99%
“…Основные характеристики 17 исследований приведены в таблице [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Изучаемые исследования различались по общему количеству пациентов.…”
Section: характеристика исследований и оценка общего риска смещенияunclassified